Lacrimal Gland Repair Using Progenitor Cells. (15th August 2016) - Gromova, Anastasia; Voronov, Dmitry A.; Yoshida, Miya; Thotakura, Suharika; Meech, Robyn; Dartt, Darlene A.; Makarenkova, Helen P.
Abstract: In humans, the lacrimal gland (LG) is the primary contributor to the aqueous layer of the tear film. Production of tears in insufficient quantity or of inadequate quality may lead to aqueous-deficiency dry eye (ADDE). Currently there is no cure for ADDE. The development of strategies to reliably isolate LG stem/progenitor cells from the LG tissue brings great promise for the design of cell replacement therapies for patients with ADDE. We analyzed the therapeutic potential of epithelial progenitor cells (EPCPs) isolated from adult wild-type mouse LGs by transplanting them into the LGs of TSP -1 −/− mice, which represent a novel mouse model for ADDE. TSP-1 −/− mice are normal at birth but progressively develop a chronic form of ocular surface disease, characterized by deterioration, inflammation, and secretory dysfunction of the lacrimal gland. Our study shows that, among c-kit-positive epithelial cell adhesion molecule (EpCAM + ) populations sorted from mouse LGs, the c-kit + dim/EpCAM + /Sca1 − /CD34 − /CD45 − cells have the hallmarks of an epithelial cell progenitor population. Isolated EPCPs express pluripotency factors and markers of the epithelial cell lineage Runx1 and EpCAM, and they form acini and ducts when grown in reaggregated three-dimensional cultures. Moreover, when transplanted into injured or "diseased" LGs, they engraft into acinar and ductal compartments. EPCP-injected TSP-1 −/− LGs showed reduction of cell infiltration, differentiation of the donor EPCPs within secretory acini, and substantial improvement in LG structural integrity and function. This study provides the first evidence for the effective use of adult EPCP cell transplantation to rescue LG dysfunction in a model system.